In vitro IL-15-activated human naïve CD8+ T cells down-modulate the CD8β chain and become CD8αα T cells - Esgalhado, André J.; Reste-Ferreira, Débora; Weinhold, Sandra; Uhrberg, Markus; Cardoso, Elsa M.; Arosa, Fernando A. (Frontiers in Immunology, 2024)
Antigen-driven human effector-memory CD8+ T cells expressing low levels of the CD8 chain have been previously described. However, little is known on a possible antigen-independent trigger. We have examined the impact that IL-15 have on the expression of CD8 on purified human naïve CD8+ T cells after CFSE labeling and culture with IL-15. As expected, IL-15 induced naïve CD8+ T cells to proliferate and differentiate. Remarkably, the process was associated with a time-dependent downmodulation of CD8 from the cell surface, leading to the generation of CD8 low and CD8 − T cells.In contrast, CD8 expression remained steady or even increased. Determination of mRNA levels for CD8 and CD8 by qPCR revealed that IL-15 promoted a significant decrease in mRNA levels of the CD8 M-4 isoform, while levels of the M-1/M-2 isoforms and of CD8 increased. Noteworthy, CD8+ T cell blasts obtained after culture of CD8+ T cells with IL-15 showed a striking increase (4.5-fold) in the level of the tyrosine kinase Lck, when compared to CD8+ T cells at day 0. This study has shown for the first time that IL-15 generates CD8 +  low and CD8 +  − T cells containing high levels of Lck, suggesting that they may be endowed with unforeseen functional features. (201 words)